KAJIAN TINGKAT KOMPLEKSITAS MASALAH PADA BUKU PEMBELAJARAN MATEMATIKA BERBASIS TAKSONOMI SOLO - Nur Asitah; Fatkul Anam; Agung Purnomo (Jurnal Muassis Pendidikan Dasar, 2022)
Mathematics is an important subject in schools, as well as among other complex subjects. Of the various difficulties of research, it is always difficult for mathematics to be the most important subject for every student. Students have difficulties that can make mistakes when working on math problems. One way to identify the appropriateness of students' responses to math problems is the SOLO taxonomy. SOLO taxonomy plays a role in determining the quality of student responses to the problems faced. Researchers used a Student Textbook entitled "Senang Belajar Matematika Untuk Siswa SD/MI Kelas 5" to classify math problems based on the SOLO taxonomy. This research is a qualitative study using content analysis. The results of the study resulted in prestructural 0%, unistructural 14.1%, multistructural 32%, relational 42.9%, and extended abstract 10.8%. The research result is also a type of mathematical problem with a scale of 156 questions. Not many types of questions with prestructural level are found in this book because the types of questions, in general, are at the beginning of the lesson which is made by the teacher himself. However, the results also show that the level of complexity of questions that are extended to abstract is not too much found in the examples of questions presented in this textbook. It is advisable to add variations to the extended abstract level question, because at this age students are already able to work on questions with a more difficult level of thinking.